Pengaruh Kualitas Layanan, Brand Image, dan Harga Terhadap Minat Beli Jasa GO-JEK pada Saat COVID-19 di Medan - Selly Juliani; Hanny Siagian; Pioner Pelawi (Jurnal Wira Ekonomi Mikroskil, 2022)
The purpose of this study was to determine and analyze the effect of service quality, brand image, and price on interest in buying GO-JEK services during COVID-19 in Medan. The type of this research used in this study was quantitative research with descriptive approach. The population in this study was the community in Medan amounted 98 respondents. The sampling technique was using a saturated sample and the number of samples in this study amounted 98 respondents. The method of data analysis used multiple linear regression analysis. The results showed that service quality and price variables have a positive and significant effect on interest in buying GO-JEK services during COVID-19 in Medan, while brand image variable has no effect on interest in buying GO-JEK services during COVID-19 in Medan. However, simultaneously variables, service quality, brand image, and price have a significant effect on interest in buying GO-JEK services during COVID-19 in Medan. The result of the coefficient of determination is 80,2%, this shows that the variables consisting of service quality, brand image, and price affect the interest in buying variables. While the remaining 19,8% is explained by other variables not explained in this study.